Short-term reuse of catheters is associated with microbiological and structural burden: A prospective pilot case series - Grasdal, Mark; Lai, Rachel; Walter, Matthias; Krassioukov, Andrei V. (Frontiers in Urology, 2022)
The aim of this pilot study was to assess the short-term microbiological burden and surface damage of catheters for intermittent catheterization (IC) in adult individuals with chronic (> 1-year) spinal cord injury (SCI). Three participants (two females, one male mean age 52 years) were asked to clean and reuse polyvinyl chloride catheters for IC over three days. Urine and catheter swab samples were collected on each day for microbiological analysis. After re-use, all catheters were analyzed via electron microscopy. Of all catheter swab cultures, 14 were negative, 12 were contaminated (i.e. skin or mixed flora), and one had growth of Haematomicrobium sanguinis. All urine cultures revealed either growth of Escherichia coli (n=10) in participants 1 and 2, or Klebsiella pneumoniae (n=4) or mixed enteric flora (n=1) in participant 3. Since all participants had asymptomatic bacteriuria with a significant number of colony-forming units per litre (CFU/L, i.e. > 100’000’000) prior to the study, we could not observe additional increases in the microbial growth (i.e. urine culture). Electron microscopy showed signs of surface damage, accumulation of debris and bacterial colonization on the exterior surface and lumen of the reused catheters. Thus, future studies should exclude participants with pre-study bacteriuria. Furthermore, a longer study duration as well as conducting electron microscopy of catheters after varied days of reuse could provide even better evidence on how structural and microbial changes of reused catheters progress over time.